MEDIASI DALAM PENYELESAIAN PERKARA PERCERAIAN PADA MASA PANDEMI COVID-19 DI PENGADILAN AGAMA MAROS - Andrianto, Moh Ifan; Sabri Samin; Muh. Jamal Jamil (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem being studied is how to mediate in the settlement of divorce cases during the COVID-19 pandemic at the Maros Religious Court from the perspective of Islamic law. This type of research is a descriptive qualitative approach with juridical, normative and sociological theology. Data collection methods used are observation, interviews and documentation. The data analysis technique used is descriptive analysis. The results of the study found that the mediation procedure at the Maros Religious Court class 1B based on PERMA Number 1 of 2016, the Covid-19 pandemic resulted in a change in procedure, namely having to do a Covid-19 test and also comply with health protocols. In 2019-2021 successful and unsuccessful mediation cases experienced ups and downs, successful mediation cases increased in 2020 and decreased in 2021, while unsuccessful mediation decreased in 2020 and increased in 2021. The Qur'an explains Conflicts and disputes that occur among human beings are a reality. Humans as caliphs on earth are required to resolve disputes.